THE PRINCIPLE OF NEWS SELECTIVITY AND VALIDITY IN ISLAM (Thematic Study of the Quran Surah Al Hujurat Verse 6) - Hanifah Muyasaroh (PROCEEDING AL GHAZALI International Conference, 2023)
The hoax phenomenon continues to spread in Indonesia, which has a Muslim population of 231.06 million (86.7%). The data from the report of the Ministry of Communication and Information Technology shows that hoax news during the pandemic reached 2,053. This phenomenon is a big question, because Muslims who all their life activities adhere to the Quran which teaches rahmatan lil alamin values, but they are still trapped in hoax that undermines national unity and integrity. This study aims to dissect the principles of selectivity and validity of news in Islam and how Muslims are able to build a selective culture of news and contribute to the suppression of hoaxes in Indonesia. The result of this research was that Muslims in Indonesia should do two things related to selectivity and validity, first, researching and selecting news sources, and second, selecting news content. If Muslims take these steps, then the number of hoax news will decrease.